The Importance of Diverse Economic Contexts in African Student Success - Inglis, Helen; Matemba, Esther; Mogashana, Disaapele (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
Existing research into student success may not be useful to develop interventions which can improve outcomes for engineering students in Africa, since they fail to account for diversity in local contexts. In our larger project we are using Grounded Theory Methodology (GTM) to investigate student success in African engineering education, interpreted through the experiences of educators. This phase of the project aims to understand better what is meant by “student success” in African engineering education, and to articulate the contexts which impact student success. We recruited participants who had at least five years’ experience in engineering education in African institutions. We conducted a focus group with three participants, and individual semi-structured interviews with four participants. The seven participants are from six African countries and include lecturers as well as academic leaders. Our findings in this paper focus on national and institutional economic contexts. National policies governing funding of university studies, as well as historic funding strategies, contribute significantly to contextual diversity. Institutional contexts include the physical and staffing resources available, whether the institution is private or state-funded, and the socio-economic status distribution of the student body. Based on our analysis of the data, we propose a model in which economic factors are understood as emerging from interactions between national, institutional and personal context.